Gerakan Anak Sehat: Sosialisasi Peran Multivitamin dalam Menjaga Kesehatan Siswa SD Negeri 1 Curut - Gigih Kenanga Sari; Novia Julianti; Rara Erika; Sindy Mellyana Putri (LPPM AN Nuur, 2026)
Background: Multivitamins are pharmaceutical preparations consisting of vitamins, either in single or combined forms, that serve to meet the nutritional needs of the body. Vitamins are essential for the human body as they play a role in metabolism, immunity, and other physiological functions. However, the human body cannot produce sufficient amounts of vitamins, making dietary intake or supplementation necessary. Objective: To enhance students' understanding of the importance of consuming multivitamins to maintain their health and prevent diseases. Method: This activity involved a socialization program conducted at SDN 1 Curut on Tuesday, December 3, with the participation of 13 students. The program included presentations and discussions focusing on the importance of consuming multivitamins. Results: The socialization activity at SDN 1 Curut, involving 13 fourth-grade students, ran smoothly and received positive feedback. Students' understanding of the importance of consuming multivitamins improved significantly after attending the session and participating in the posttest. The activity also received good appreciation from the participants. Conclusion: The socialization regarding the importance of consuming multivitamins successfully enhanced the understanding of the fourth-grade students at SDN 1 Curut. The majority of the students demonstrated high enthusiasm and better comprehension of the benefits of multivitamins in maintaining body health.